2020
DOI: 10.1177/1060028020943569
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Intravenous Push Lacosamide Compared With Intravenous Piggyback at a Tertiary Academic Medical Center

Abstract: Background: There are limited data regarding the incidence of adverse events associated with administering lacosamide by intravenous push (IVP) compared with IV piggyback (IVPB). Objective: The objective of this analysis was to compare the safety profile, including cardiovascular effects, sedative effects, and IV site reactions of IVP and IVPB lacosamide administration. Methods: A retrospective pre/post cohort analysis comparing patients who received lacosamide via IVP and IVPB was conducted. Safety end points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 9 publications
1
22
1
Order By: Relevance
“…Hypotension was defined as a systolic blood pressure (SBP) <90 mm Hg or a reduction of ≥30% from baseline blood pressure. 13 Bradycardia was defined as a heart rate (HR) <50 beats per minute (BPM) or a reduction of ≥30% from baseline HR. 13 For hypotensive and bradycardic events, the SBP and HR values used were defined as the closest measured value within 6 hours prior to and following olanzapine administration.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hypotension was defined as a systolic blood pressure (SBP) <90 mm Hg or a reduction of ≥30% from baseline blood pressure. 13 Bradycardia was defined as a heart rate (HR) <50 beats per minute (BPM) or a reduction of ≥30% from baseline HR. 13 For hypotensive and bradycardic events, the SBP and HR values used were defined as the closest measured value within 6 hours prior to and following olanzapine administration.…”
Section: Methodsmentioning
confidence: 99%
“…13 Bradycardia was defined as a heart rate (HR) <50 beats per minute (BPM) or a reduction of ≥30% from baseline HR. 13 For hypotensive and bradycardic events, the SBP and HR values used were defined as the closest measured value within 6 hours prior to and following olanzapine administration. Baseline SBP and HR values less than 90 mm Hg or 50 BPM, respectively, were not included for assessment of hypotension or bradycardia after the respective administration of olanzapine.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was known for another old SCB-ASM, phenytoin ( 16 ). There were limited data on the cardiac safety of intravenous LCM ( 6 , 17 , 18 ). A Korean study that focused on the cardiac safety of rapid intravenous LCM suggested a relatively higher rate (32.9%) of cardiac adverse event, especially the new-onset first-degree atrioventricular block (22.4%) ( 6 ).…”
Section: Introductionmentioning
confidence: 99%